The Implementation of Digital Marketing at Penta Buana Media - Nurvia Nathasya; Anita Miranda; heri setiawan; sari lestari zainal ridho (International Journal of Advanced Research in Social Studies, 2022)
This project research aims to implement video marketing, which is one of the digital marketing techniques, at Penta Buana Media. Digital marketing is implemented to promote Penta Buana Media in a larger market, by utilizing the internet. Video marketing technique is one of the marketing media that is in great demand by business people because this technique has been neatly conceptualized, and can provide explanations by showing pictures and sound simultaneously, making it easier to understand. In the process of implementing digital marketing, the author uses a mind mapping method which is divided into 3 (three) stages. The first is the planning stage, consisting of literature studies, interviews, and observations. Next is the planning and development stage, consisting of the video marketing design stage and situation analysis with a SWOT identification to identify existing strengths, weaknesses, threats and opportunities. And the last stage is uploading a marketing video on Penta Buana Media's Instagram, in an effort to complete the digital marketing project that the author is doing.